Modern trends of education development and mathematical training of schoolchildren - Oleg Konstantinovich Podlipsky (Вестник Майкопского государственного технологического университета)
The relevance of the research is due to the need to modernize mathematical training of schoolchildren in line with the key trends in the development of education: globalization, digitalization and population aging. Conceptual ideas ensuring the development of modern mathematical theories have been identified on the basis of the analysis, and a set of key elements that make up the base of modern mathematics have been presented: structures, properties, actions, abstractions, relationships, behavior and alternatives. The research problem is to determine the foundations of designing a system of mathematical education, focused on students gaining a broad understanding of mathematics as a cultural phenomenon, a language of science and a set of tools for real life. The purpose of the study is to describe ways to modernize the mathematical preparation of schoolchildren in the mainstream of digitalization and the practical orientation of education. In the research process the following methods have been used: study and analysis of literary sources, theoretical modeling and design. One of the most significant manifestations of the digitalization trend in mathematical education is the use of interactive geometric environments. Their technical and methodological capabilities make it possible to organize the process of teaching mathematics on the basis of a research approach, which is expressed in students independently putting forward hypotheses in the process of experimenting with geometric objects created in an interactive geometric environment. The necessity of including mathematical literacy as one of its important results in the mathematical preparation of schoolchildren has been justified. The necessary changes in the content of mathematical training have been determined by creating a system of special, competency-based tasks.